How Pakistan's media spreads the message about reproductive and sexual health. (16th March 2015) - Abidi, Syed H; Raees, Muhammad; Ali, Syed
Abstract : Liberalising influences in the past 20 years have led to a media policy that may have helped improve reproductive and sexual health in the country, say Syed H Abidi, Muhammad Raees, and Syed Ali